2014
DOI: 10.4049/jimmunol.1303369
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Intestinal Inflammation by Bacterial Exopolysaccharides

Abstract: Host inflammatory responses against pathogenic organisms can be abrogated by commensals; however, the molecular mechanisms by which pathogenesis is prevented are still poorly understood. Previous studies demonstrated that administration of a single dose of Bacillus subtilis prevented disease and inflammation by the enteric mouse pathogen Citrobacter rodentium, which causes disease similar to the human pathogen enteropathogenic E. coli. No protection was observed when an exopolysaccharide (EPS)-deficient mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
75
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 34 publications
2
75
0
1
Order By: Relevance
“…All protective strains were capable of producing EPS as part of their biofilm matrix, leading us to suggest that EPS is the protective molecule of B. subtilis. Consistent with this idea, we purified EPS from a B. subtilis strain that overproduced soluble EPS and found that it alone was sufficient to prevent disease [35] . Carbohydrate analysis revealed that B. subtilis EPS is comprised of 3 sugars, mannose (88%), glucose (11.9%) and N-acetyl-glucosamine (<0.1%) with linkages as described [35] .…”
Section: Immunomodulation By Bacillus Subtilis Eps: Macrophagesmentioning
confidence: 64%
See 4 more Smart Citations
“…All protective strains were capable of producing EPS as part of their biofilm matrix, leading us to suggest that EPS is the protective molecule of B. subtilis. Consistent with this idea, we purified EPS from a B. subtilis strain that overproduced soluble EPS and found that it alone was sufficient to prevent disease [35] . Carbohydrate analysis revealed that B. subtilis EPS is comprised of 3 sugars, mannose (88%), glucose (11.9%) and N-acetyl-glucosamine (<0.1%) with linkages as described [35] .…”
Section: Immunomodulation By Bacillus Subtilis Eps: Macrophagesmentioning
confidence: 64%
“…Consistent with this idea, we purified EPS from a B. subtilis strain that overproduced soluble EPS and found that it alone was sufficient to prevent disease [35] . Carbohydrate analysis revealed that B. subtilis EPS is comprised of 3 sugars, mannose (88%), glucose (11.9%) and N-acetyl-glucosamine (<0.1%) with linkages as described [35] . The composition of this EPS contrasts with that reported previously [34] , and additional studies are needed to identify which sugar moieties and linkages are critical for protection.…”
Section: Immunomodulation By Bacillus Subtilis Eps: Macrophagesmentioning
confidence: 64%
See 3 more Smart Citations